Outcomes After Heart Transplantation for Amyloid Cardiomyopathy in the Modern Era. Issue 3 (3rd February 2015) - Davis, M. K.; Kale, P.; Liedtke, M.; Schrier, S.; Arai, S.; Wheeler, M.; Lafayette, R.; Coakley, T.; Witteles, R. M.
<x xml:space="preserve">Abstract</x> We conducted a review of patients undergoing heart transplantation (HT) at our institution for amyloid cardiomyopathy (ACM) between 2008 and 2013. Complete follow‐up was available for all patients. Nineteen patients with ACM underwent HT during the study period, accounting for 9.4% of all HT performed at our institution during this period. Amyloid subtype was light chain (AL) in 9 patients and transthyretin (ATTR) in 10 (2 wild‐type, 7 familial, 1 unknown). Eight of nine patients with AL amyloidosis began chemotherapy prior to HT, six have resumed chemotherapy since HT, and five have undergone autologous stem cell transplantation. Most recent free light chain levels in AL patients decreased by a median of 85% from peak values. Only one patient developed recurrent graft amyloidosis, occurring at 3.5 years post‐HT and asymptomatic. After a median follow‐up of 380 days, 17 (89.5%) patients are alive. To our knowledge, this is the largest single‐center series reported of ACM patients undergoing HT in the modern era. Our results suggest that acceptable outcomes following HT can be achieved in the short‐to‐intermediate term and that this is a feasible option for end‐stage ACM with careful patient selection and aggressive control of amyloidogenic light chains in AL patients.